“Merdeka Belajar”: A Cultural Political Economy of Indonesia’s Neoliberalising Nationalist University - Rakhmani, Inaya (UI Scholars Hub, 2024)
This article examines the realignment of nationalist higher education in Indonesia to suit market interests. Using a cultural political economy approach to knowledge and power, this article selects and analyses university policy reforms and narratives in Indonesia that have guided university reform in the past decades. It suggests that the reorganisation of Indonesia’s higher education sector can be understood through the relationship between structural change in the global economy, which occurs together with cultural shifts within national and local conditions. It looks at how universities and higher education policies are organised in post-authoritarian Indonesia under the framework of neoliberal governance, which prioritises producing knowledge that aligns with the market imperatives. It argues that the marketisation of higher education discursively and materially reconfigures New Order-style development planning and stylises it into ways that accommodate neoliberal demands.